2014
DOI: 10.5901/mjss.2014.v5n6p273
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the Study Habits of Distance Learners: Implications for Guidance and Counseling Services

Abstract: This study looked at the study habits of University of Cape Coast Distance Education learners in the Cape Coast Study Centre in the Central Region of Ghana. Descriptive survey design was used to conduct the study. Stratified and simple random sampling procedures were used to select 338 Business and Education distance learners. A self-designed questionnaire, which consisted of 40 items, was used to collect data from the respondents. Data collected was analysed by the use of descriptive (frequencies and percenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…In Pakistan, the concept of studying in libraries is minimal therefore, students rely to studying at their home which has also been confirmed by Somuah et al 29 After the analysis, no relationship between chosen studymethod and the grouping of students was found. Vacha 32 reported that cramming was an effective studying tactic for courses that use take-home essay exams and research papers as significant parts of the course grade.…”
mentioning
confidence: 59%
“…In Pakistan, the concept of studying in libraries is minimal therefore, students rely to studying at their home which has also been confirmed by Somuah et al 29 After the analysis, no relationship between chosen studymethod and the grouping of students was found. Vacha 32 reported that cramming was an effective studying tactic for courses that use take-home essay exams and research papers as significant parts of the course grade.…”
mentioning
confidence: 59%
“…Distance learners need to know how much time to spend on a given learning package, when it is permissible to take a break in their studies and when they need to pick them up again. Open learners' study at their own pace (Somuah, Dankyi & Dankyi, 2014). Those experienced in ODL will know, though, that completely open-ended study is rarely effective.…”
Section: Unpacking Self-learning Materialsmentioning
confidence: 99%
“…Distance education has long been associated with unsatisfied academic performance [1]. This problem has been the biggest drawback facing this form of education all over the world.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Globally, the adjustment difficulties of distance learners have been an emerging issue, especially their ability to adapt to the existing university structures that were designed for regular students. Unlike regular students, distance students are usually older, have jobs, family responsibilities and mostly might have been away from their books for a longer period which make adjustment very difficult [1]. Many studies have proved that the adjustment difficulties like appetite disturbance, concentration problems, stress and depression are most evident in fresh distance learners [2].…”
Section: Introductionmentioning
confidence: 99%